Nanoscale control of Si nanoparticles within a 2D hexagonal array embedded in SiO2 thin films. (29th November 2016) - Castro, Celia; BenAssayag, Gérard; Pecassou, Béatrice; Andreozzi, Andrea; Seguini, Gabriele; Perego, Michele; Schamm-Chardon, Sylvie
Abstract: In this work, we investigate the ability to control Si nanoparticles (NPs) spatially arranged in a hexagonal network of 20 nm wide nanovolumes at controlled depth within SiO2 thin films. To achieve this goal an unconventional lithographic technique was implemented based on a bottom-up approach, that is fully compatible with the existing semiconductor technology. The method combines ultra-low energy ion beam synthesis with nanostructured block-copolymer thin films that are self-assembled on the SiO2 substrates to form a nanoporous template with hexagonally packed pores. A systematic analytical investigation using time of flight-secondary ion mass spectroscopy and low-loss energy filtered transmission electron microscopy demonstrates that by adjusting few fabrication parameters, it is possible to narrow the size distribution of the NPs and to control the number of NPs per nanovolume. Experimental results are critically discussed on the basis of literature data, providing a description of the mechanism involved in the formation of Si NPs.